Os consórcios públicos de saúde e seu impacto no desenvolvimento dos municípios goianos - Calil, Taric (2018)
The present study analyzes the influence of the public health consortium on the development of the municipalities of Goiás. The great autonomy given to municipalities in the period of redemocratication was initially accompanied by the decentralization of public policies, so that local power became responsible for the provision of increasingly public services. Although, the fiscal resources, which were also decentralized in principle, were once again concentrated under the control of the Central Government, gradually choking municipal income. All this movement forced local governments to find alternatives that would enable the execution of public services without compromising their financial health, as determined by the Fiscal Responsibility Law. It is in this direction that the public consortium appears as an instrument of cooperation between federated entities for the management of public policies of common interest. Thus, a detailed study is carried out on the public consortium, its concepts, historical trajectory, legislation, relevant statistical data and finally the analysis of the impact of the presence of public health consortium on Firjan Index of Municipal Development (health dimension) at the municipalities of Goiás.